ASSESSMENT OF ERYTHROCYTE PERIPHERAL BLOOD AND ACTIVITY OF HEMOST ASIS IN PATIENTS WITH CER VICAL CANCER - N. I. Stuklov; T. V. Sushinskaya (Исследования и практика в медицине)
Despite the availability and informative value of methods that facilitate the diagnosis, cervical cancer (CC) does not lose its leading position as one of the most common cancers of the reproductive system in women worldwide. High prevalence of anemia and thrombotic complications in this group determines not only the quality of life of patients, but the outcome of the underlying disease. The purpose of the study was to determine the patterns of change in erythrocyte of peripheral blood and the state of vascular-platelet and coagulation hemostasis in patients with cervical cancer depending on the stage of disease and histological variant of the tumor.Materials and methods. We investigated the performance of erythron, thrombocytic and coagulation hemostasis in 74 patients with cervical cancer (mean age 46,49 ± 11,78 years). Blood analysis was performed in the initial evaluation of patients in the prehospital phase.Results. It is proved that the spread of the tumor outside the cervix exerts a systemic influence on hematopoiesis, hemostasis, significantly increasing the risk of venous thromboembolism and hematogenous dissemination of the disease (metastasis). In the case of adenocarcinoma and dimorphic (glandular-squamous) cervical cancer we proved the significant increase in soluble fibrin-monomer complexes, fibrinogen, and with glandular-squamous-cell cervical cancer and hypercoagulability (decrease thrombin time), which requires mandatory and differentiated prevention of venous thromboembolism even in the early stages of these morphological variants of the disease.Conclusions. Cervical cancer has a systemic effect on the blood and hemostasis. A statistically significant decrease in the concentration of hemoglobin and increased erythrocyte sedimentation rate is determined in the second stage of the disease. The increase in the prevalence of cervical cancer and the presence of glandular component in the morphological structure of the tumor was significantly associated with increased thrombosis.